Association between maternal family history of hypertension and preterm birth: modification by noise exposure and multivitamin intake. (30th December 2022) - Sun, Jia; Yang, Rong; Xian, Hong; Zhang, Bin; Lin, Hualiang; Xaverius, Pam; Yang, Shaoping; Dong, Guang-Hui; Howard, Steven W.; LeBaige, Morgan; Peng, Anna; Liu, Echu; et al.
Abstract: Objective: To measure the effect of maternal family history of hypertension on preterm birth (PTB) and to identify factors that modified this association. Methods: A case-control study was nested in a prospective cohort of the entire pregnant population in Wuhan, China, from 2011 to 2013. Home-visit interviews were scheduled for all PTBs and their controls, to collect extensive information on maternal exposures to behavioral, environmental, and intergenerational risk factors of PTB. The effects of maternal family history of hypertension on PTB were measured by logistic regression analyses, controlling for potential confounders. Potential effect modifiers were examined using stratified analyses. Results: There were 2393 PTBs and 4263 full-term births out of all eligible births. A positive association was observed between maternal family history of hypertension and PTB, after adjusted for potential confounders (adjusted odds ratio: 1.17 [1.03, 1.33]). A higher effect was observed when mothers were exposed to certain noise during pregnancy (adjusted odds ratio: 1.37 [1.14, 1.65]) and/or when they did not take multivitamins during pregnancy (adjusted odds ratio: 1.46 [1.20, 1.78]), whereas, this association was weaker and no longer significant when mothers took multivitamins during pregnancy (adjusted odds ratio: 1.00 [0.84, 1.19]) and/or when they were not exposed to certain noise during pregnancy (adjusted odds ratio: 1.01 [0.85, 1.12]). The modification effect from maternal multivitamin intake was significant on both spontaneous and medically indicated PTBs, and the modification effect from maternal exposure to certain noise was only significant on spontaneous PTB. Conclusions: Increased PTB risk was observed for pregnant women with a family history of hypertension in Wuhan, China. This effect was stronger when pregnant women did not take multivitamin and/or exposed to certain noise during pregnancy, than those who took multivitamin and/or unexposed to certain noise.